Pertanggungjawaban Penyidik Kepolisian Terhadap Penangkapan Error In Persona Ditinjau Dari Hukum Indonesia Dan Singapura - Yudhi Priyo Amboro; Diki Diki (Journal of Judicial Review, 2014)
The purpose of this study is to describe clearly and carefully about accountability kepolisi investigator in the case of error in terms of the legal persona Indonesian and SingaporeThis type of research is the study of normative law. Normative research study only to legal writing and books, also called the research literature. In this study will be more use of secondary data and primary data used as complement to the data.In this thesis consists of: primary legal materials, legal materials and secondary legal. Data mining is done with the study of literature and. Once all the data is collected both primary data and secondary data, the data is then processed and analyzed, the qualitative analysis was used to group the data point by the studied aspects.Based on the resultsof this study indicate that there is aprovision inabook of the lawof criminal procedure regarding the action so therwise permitted under investigation for quality regulation sandliability for the occurrence of errorin persona in terms of the laws of Indonesia and Singapore.